Evidence of chikungunya virus infections among febrile patients at three secondary health facilities in the Ashanti and the Bono Regions of Ghana. - Jonathan Akwasi Adusei; Patrick Williams Narkwa; Michael Owusu; Seth Agyei Domfeh; Mahmood Alhassan; Emmanuel Appau; Alimatu Salam; Mohamed Mutocheluh (Public Library of Science (PLoS), 2021)
Background Chikungunya is now of public health concern globally due to its re-emergence in endemic areas and introduction into new areas of the world. Worldwide, the vectors for transmission of the chikungunya virus are Aedes mosquitoes and these are prevalent in Ghana. Despite its global significance, the true burden of chikungunya virus infection in Ghana is largely unknown and the threat of outbreak remains high owing to international travel. This study sought to determine chikungunya virus infection among febrile patients suspected of having malaria infections at some selected health facilities in the Ashanti, Bono East, and Bono Regions of Ghana. Methodology This cross-sectional study recruited six hundred (600) febrile patients suspected of having malaria who submitted their clinical samples to the laboratories of the selected health facilities for the diagnosis of their infections. Five to ten millilitres (5-10ml) of venous blood were collected from each study participant. Sera were separated and tested for anti-chikungunya (IgM and IgG) antibodies using InBios ELISA kit following the manufacturer's instruction. Samples positive for chikungunya IgM and IgG were selected and tested for chikungunya virus RNA using Reverse Transcription-quantitative Polymerase Chain Reaction. Malaria Rapid Diagnostic Test kits were used to screen the participants for malaria. Structured questionnaires were administered to obtain demographic and clinical information of the study participants. Result Of the 600 samples tested, the overall seroprevalence of chikungunya was 6%. The seroprevalence of chikungunya IgM and IgG antibodies were 1.8% and 4.2% respectively. None of the chikungunya IgM and IgG positive samples tested positive for chikungunya RNA by RT-qPCR. Of the 600 samples, tested 32.3% (194/600) were positive for malaria parasites. Malaria and chikungunya co-infection was detected in 1.8% (11/600) of the participants. Conclusion Findings from the current study indicate low-level exposure to the chikungunya virus suggesting the virus is circulating and potentially causing morbidity in Ghana.